Nanoparticle-GFP “chemical nose” sensor for cancer cells identification - Moyano, Daniel F. (2013)
Nanoparticle-based sensor arrays have been used to distinguish a wide range of bio-related molecules through pattern recognition. This “chemical nose” approach uses nanoparticles as receptors to selectively identify the analytes, while a transducer reports the binding through a readable signal (fluorescence). Here we describe a procedure that uses functionalized gold nanoparticle as receptors and Green Fluorescent Protein (GFP) as the transducer to identify and differentiate cell state (normal, cancerous, and metastatic), an important tool in early diagnosis and treatment of tumors.